Converting cellulose nanocrystals into photocatalysts by functionalisation with titanium dioxide nanorods and gold nanocrystals. Issue 61 (8th October 2020) - Nair, Santhosh S.; Chen, Jianhong; Slabon, Adam; Mathew, Aji P.
Abstract : Cellulose nanocrystals (CNCs) are promising building blocks for water purification due to their high surface area, tuneability of surface charge and grafting of surface groups depending on the pollutants. Abstract : Cellulose nanocrystals (CNCs) are promising building blocks for water purification due to their high surface area, tuneability of surface charge and grafting of surface groups depending on the pollutants. In this report we have converted CNCs into photocatalysts, without altering the surface groups, by in situ growth of TiO2 nanorods (NRs) and functionalization with Au nanocrystals (NCs) for enhanced light absorption. The control of the density of the NRs assures that the CNC surface and functionalities are accessible for the pollutant, followed by the photocatalytic degradation on the light absorption layer under solar illumination. This seed-mediated NR synthesis can be applied to realize a series of CNC-inorganic NR photocatalysts. The low temperature (90 °C compared to commonly reported growth at 150 °C) of the NR growth provides the opportunity to use nanostructured biopolymers as functional substrates for preparation of photocatalysts using a bio-inspired design.